HAK DAN TANGGUNG JAWAB ATAS LINGKUNGAN HIDUP (Sebuah Pendekatan Etika Lingkungan Hidup) - Norbertus Jegalus (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2021)
Environmental ethics are born out of an environmental crisis. Basically, humans are part of nature. That's why environmental problems are human problems. Humans are really aware that the main problem of human life today is not a matter of running out or limiting natural resources, but rather a matter of increasingly severe natural damage. It is becoming increasingly recognized that the depletion of natural resources may still be offset by the discovery of new technologies. Therefore, the matter of limitation or depletion of natural resources because they are managed by humans is not a matter of life or death. As for the matter of life or death for us today is the environmental crisis. So, a more urgent problem is the environmental damage which is already so concerning, especially the environment in urban areas. What absolutely must be limited is the increasing pressure on ecological systems due to the negative effects of human activities. The capacity of nature to accommodate the pressures of air pollution and water pollution, land degradation in cities cannot be matched by new technology.